2022
DOI: 10.1177/15280837221128314
|View full text |Cite
|
Sign up to set email alerts
|

A review on developments of in-vitro and in-vivo evaluation of hybrid PCL-based natural polymers nanofibers scaffolds for vascular tissue engineering

Abstract: The main objective of the present review article is to investigate the in-vitro and in-vivo biocompatibility behavior of hybrid PCL-based scaffolds with collagen, gelatin, and chitosan to improve endothelialization for VTE applications. It is reported that the high-rate failure of small diameters vascular grafts (SDVGs, <6 mm) due to adhesion of platelets and plasma protein and aggregation, over-proliferation of smooth muscle cells (SMCs), and neointimal hyperplasia at the implantation site is main challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 169 publications
(244 reference statements)
0
2
0
Order By: Relevance
“…PCL, on the other hand, is a viscous nontoxic polymer that shows a good mechanical properties. 9,10 Both of these two polymers are biodegradable with semicrystalline structures, which is important in designing biomaterials scaffolds. 11 It has been confirmed that a simple artificial pulley should transfer the mechanical forces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCL, on the other hand, is a viscous nontoxic polymer that shows a good mechanical properties. 9,10 Both of these two polymers are biodegradable with semicrystalline structures, which is important in designing biomaterials scaffolds. 11 It has been confirmed that a simple artificial pulley should transfer the mechanical forces.…”
Section: Introductionmentioning
confidence: 99%
“…PU is known as an elastic polymer with soft and hard segments, and it has bioactive and biocompatible properties. , PU is a less hydrophobic and more flexible polymer than PCL. PCL, on the other hand, is a viscous nontoxic polymer that shows a good mechanical properties. , Both of these two polymers are biodegradable with semicrystalline structures, which is important in designing biomaterials scaffolds . It has been confirmed that a simple artificial pulley should transfer the mechanical forces .…”
Section: Introductionmentioning
confidence: 99%